Front Matter for Volume 102, Issue 2 - David L Doerfert (Journal of Applied Communications, 2018)
Overview of the Journal of Applied Communications is provided including the aim and scope of the journal, the list of Editorial Board members, and manuscript submission guidelines. The mission of and the board of directors for the Association for Communication Excellence in Agriculture, Natural Resources, and Life and Human Sciences (ACE) is also included.